BAHASA BALI DALAM PENGEMBANGAN PENGETAHUAN (PERSPEKTIF PENGETAHUAN ETIKA DAN ESTETIKA) - I Made Suweta (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2020)
As the center of culture, the Balinese language acts as a civilization builder. Building a civilization is synonymous with building humans, which includes building ethics and aesthetics. As cultured creatures, humans are very concerned about the development of ethics and aesthetics properly for the existence of human civilization itself. Balinese language in this case will accommodate the development of ethics and aesthetics, seen from the Balinese language used as a means of communication that is polite and polite as well as the existence of aesthetic diction in social life in society. There are two important things that will be discussed in this paper, namely: How is the Balinese language in the development of ethical knowledge? and how is the Balinese language in the development of aesthetic knowledge? Based on a glimpse of the background of the Balinese language when it is associated with ethics and aesthetics, the results of the discussion can be presented as described below. (1) Balinese language as a developer of ethical knowledge, which can be used in social behavior, as seen from the words that have the value of respect; either to respect the interlocutor or to humiliate the speaker (basa Bali alus singgih, basa Bali alus sor, basa Bali alus madya, and basa Bali alus mider). (2) Balinese language as a developer of aesthetic knowledge, which can be used in art, so that human life will be happier because it can be entertained from the existence of Balinese language that contains beauty (mabebasan tradition in pesantian, modern Balinese poetry, Balinese songs as a form of musicalization of Balinese poetry, novels and short stories containing intrinsic and extrinsic beauty values, and Balinese language in the art of calligraphy/rerajahan).